Flexible growing rods: a pilot study to determine if polymer rod constructs may provide stability to skeletally immature spines - Bylski-Austrow, Donita I (Scoliosis, 2015)
BACKGROUND: Surgical treatments for early onset scoliosis (EOS), including growing rod constructs, involve many complications. Some are due to biomechanical factors. A construct that is more flexible than current instrumentation systems may reduce complications. The purpose of this preliminary study was to determine spine range of motion (ROM) after implantation of simulated growing rod constructs with a range of clinically relevant structural properties. The hypothesis was that ROM of spines instrumented with polyetheretherketone (PEEK) rods would be greater than metal rods and lower than noninstrumented controls. Further, adjacent segment motion was expected to be lower with polymer rods compared to conventional systems. METHODS: Biomechanical tests were conducted on 6 skeletally immature porcine thoracic spines (domestic swine, 35-40 kg). Spines were harvested after death from swine that had been utilized for other studies (IACUC approved) which had not involved the spine. Paired pedicle screws were used as anchors at proximal and distal levels. Specimens were tested under the following conditions: control, then dual rods of PEEK (6.25 mm), titanium (4 mm), and CoCr (5 mm) alloy. Lateral bending (LB) and flexion-extension (FE) moments of ±5 Nm were applied. Vertebral rotations were measured using video. Differences were determined by two-tailed t-tests and Bonferroni correction with four primary comparisons: PEEK vs control and PEEK vs CoCr, in LB and FE (α=0.05/4). RESULTS: In LB, ROM of specimens with PEEK rods was lower than control at each instrumented level. ROM was greater for PEEK rods than both Ti and CoCr at every instrumented level. Mean ROM at proximal and distal noninstrumented levels was lower for PEEK than for Ti and CoCr. In FE, mean ROM at proximal and distal noninstrumented levels was lower for PEEK than for metal. Combining treated levels, in LB, ROM for PEEK rods was 35% of control (p<0.0001) and 270% of CoCr rods (p<0.01). In FE, ROM with PEEK was 27% of control (p<0.001) and 180% of CoCr (p<0.01). CONCLUSIONS: PEEK rods decreased flexibility versus noninstumented controls, and increased flexibility versus metal rods. Smaller increases in ROM at proximal and distal adjacent motion segments occurred with PEEK compared to metal rods, which may help decrease junctional kyphosis. Flexible growing rods may eventually help improve treatment options for young patients with severe deformity.